Measurement of the (anti-)He-3 elliptic flow in Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; Martin, Nicole Alice; et al. (Physics letters, 2020)
The elliptic flow (v(2)) of (anti-)He-3 is measured in Pb-Pb collisions at root s(NN) = 5.02TeV in the transverse-momentum (p(T)) range of 2-6 GeV/c for the centrality classes 0-20%, 20-40%, and 40-60% using the event-plane method. This measurement is compared to that of pions, kaons, and protons at the same center-of-mass energy. A clear mass ordering is observed at low p(T), as expected from relativistic hydrodynamics. The violation of the scaling of v(2) with the number of constituent quarks at low p(T), already observed for identified hadrons and deuterons at LHC energies, is confirmed also for (anti-)He-3. The elliptic flow of (anti-)He-3 is underestimated by the Blast-Wave model and overestimated by a simple coalescence approach based on nucleon scaling. The elliptic flow of (anti-)He-3 measured in the centrality classes 0-20% and 20-40% is well described by a more sophisticated coalescence model where the phase-space distributions of protons and neutrons are generated using the iEBE-VISHNU hybrid model with AMPT initial conditions. (C) 2020 European Organization for Nuclear Research. Published by Elsevier B.V.
Gesehen am 03.05.2021
The ALICE collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, S. Klewin, M.K. Köhler, L. Leardini, N.A. Martin, A. Ohlson, Y.C. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, J. Stachel, D. Weiser, B. Windelband, A. Yüncü [und 1009 weitere]
4201 Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt, die Zahl 3 ist hochgestellt